Patients’ Experiences About Exercise Prescription and Education in the Physiotherapy Management of Nonspecific Low-Back Pain - Omoyemi O Ogwumike PhD; Fatima Bashir-Bello MSc; Bashir Kaka PhD (Journal of Patient Experience, 2020)
Low-back pain (LBP) is highly prevalent in the society, and its socioeconomic consequences are quite evident. Physiotherapists play a prominent role in the management of individuals with this condition, and it is, therefore, of utmost importance that physiotherapists engage in the most efficient and effective management practices available. For perceptions of good performance and quality health care, patient experience is an important indicator of effective care and management. A mixed-methods research design—a cross-sectional survey (quantitative research) and a focus group discussion (FGD; qualitative research)—was employed in this study, investigating patients’ experience in physiotherapy management of nonspecific LBP. An adapted questionnaire was used for data collection from purposively selected participants recruited from 3 hospitals in Kubwa, Abuja, from April to August 2018. The FGD involved 6 patients recruited by simple random sampling using the fishbowl technique. Descriptive and thematic analyses were done on data collected. A total of 126 patients (male = 41, female = 85) were included, with a mean age of 51.0 ± 14.6 years, while the modal age-group was 60 to 69 years. Of these, 41 (32.5%) had nonspecific LBP for less than a year, and the 2 most applied interventions were exercise and heat therapy, followed by education/advice. In all, 110 (87.3%) reported positive experience about education, while 119 (94.4%) reported positive experience about exercise prescription. The result from the qualitative research is in conformity with that of the quantitative analysis. Patients with nonspecific LBP received adequate education regarding their condition and had good experience in the course of their physiotherapy management.